Lyme Borreliosis - Hunfeld, Klaus-Peter.; Gray, Jeremy; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is a compact clinical introduction to Lyme borreliosis for physicians of all specialties who care for patients with suspected B. burgdorferi infection, whether in hospital or general practice. The book provides a great deal of practice-oriented information on symptomatology, diagnosis, treatment, and prophylaxis with a special emphasis on the situation in Europe. At the same time, it describes contemporary scientific knowledge in as much detail as is required in order to understand the pathogenetic relationships and their relevance to medical care. The authors are members of an interdisciplinary expert group of epidemiologists, biologists, microbiologists, and clinicians who have been working in the area of tick-borne diseases for many years. The personal experience of each of the authors, accumulated through their daily work with patients in special clinics or by confrontation with complicated questions in basic research, epidemiology, and laboratory diagnostics of Lyme borreliosis, represents an important mainstay of the book. Written from the perspective of clinical management and practical problem-solving, this topical monograph will assist clinicians in meeting diagnostic challenges and providing appropriate medical aid to patients with Lyme borreliosis.
Chapter 1) Characteristics of Borrelia burgdorferi sensu lato -- Chapter 2) Tick Ecology and Eco-epidemiology of Borrelia burgdorferi sensu lato -- Chapter 3) Pathogenesis and Immune Defense -- Chapter 4) The History, Epidemiology, Clinical Manifestations and Treatment of Lyme Borreliosis -- Chapter 5) Special Aspects of Lyme Borreliosis in the United States -- Chapter 6) Laboratory Diagnosis of Lyme Borreliosis -- Chapter 7) Prophylactic Measures Including Future Perspectives -- Chapter 8) Public Health Aspects of Lyme Borreliosis - The German Experience -- Chapter 9) Other Ixodes-Borne Diseases.
Keywords: Epidemiology; Medical microbiology; Medicine; Epidemiology; Medical Microbiology; Clinical Medicine; Lyme Disease